2006
DOI: 10.1073/pnas.0510869103
|View full text |Cite|
|
Sign up to set email alerts
|

A bifunctional tRNA import receptor from Leishmania mitochondria

Abstract: In kinetoplastid protozoa, import of cytosolic tRNAs into mitochondria occurs through tRNAs interacting with membrane-bound proteins, the identities of which are unknown. The inner membrane RNA import complex of Leishmania tropica contains multiple proteins and is active for import in vitro . RIC1, the largest subunit of this complex, is structurally homologous to the conserved α subunit of F1 ATP synthase. The RIC1 gene complemented an atpA mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 30 publications
1
89
1
Order By: Relevance
“…One possibility is that BFs require the COII protein either for complex IV function or for an unknown function. Such an unknown function may be analogous to that of ATP synthase complex, since it functions in reverse in BFs compared to PFs (53), and its ␣ subunit has been reported to actively import tRNAs into Leishmania mitochondria (20). Alternatively, the lethality may reflect loss of editing of other mRNAs, as suggested above, or KREN3 may have an additional unknown function such as cleavage of polycistronic maxicircle or minicircle transcripts (21).…”
Section: Discussionmentioning
confidence: 91%
“…One possibility is that BFs require the COII protein either for complex IV function or for an unknown function. Such an unknown function may be analogous to that of ATP synthase complex, since it functions in reverse in BFs compared to PFs (53), and its ␣ subunit has been reported to actively import tRNAs into Leishmania mitochondria (20). Alternatively, the lethality may reflect loss of editing of other mRNAs, as suggested above, or KREN3 may have an additional unknown function such as cleavage of polycistronic maxicircle or minicircle transcripts (21).…”
Section: Discussionmentioning
confidence: 91%
“…Whether this putative receptor belongs to the TOM complex or not is an interesting question to answer in the future. Furthermore, an RNA import complex, including two bifunctional respiratory proteins, isolated from L. tropica inner mitochondrial membrane is implicated in tRNA import (12,13). However, because of the conflicting data reported so far (see above), identification of import factors in other trypanosomatids might help in understanding the complexity of mitochondrial tRNA import.…”
Section: Discussionmentioning
confidence: 99%
“…A 15-kDa putative import tRNA receptor has been reported in L. tropica, but this protein remains to be identified (10). More recently, it has been shown in L. tropica that a multisubunit RNA import complex (RIC) located on the inner mitochondrial membrane is implicated in tRNA import (11) and two subunits, RIC1 (a structural homologue to the ␣ subunit of F1 ATP synthase) and RIC8 (an homologue to subunit 6b of ubiquinol cytochrome c reductase) were identified (12,13). However, considering the contradictory data obtained so far, a deeper understanding of the import factors involved in different trypanosomatids will be important in the future.…”
mentioning
confidence: 99%
“…The potential problem of an imbalanced matrix tRNA pool is solved by the unique phenomenon of allosteric regulation; type I RNAs stimulate the inner membrane transfer of type II RNAs, whereas type II RNAs inhibit transfer of type I (11,12 (11)(12)(13); in vitro evolution experiments suggest that many more tRNA species belong to these categories (11). The "ping-pong" model (14) postulates that the two types of tRNA bind to different receptors; binding of type I tRNA to its receptor induces a conformational change that is transmitted to the type II receptor, opening up its tRNAbinding site.…”
Section: From the Genetic Engineering Laboratory Indian Institute Ofmentioning
confidence: 99%
“…Two tRNA-binding proteins with the properties of type I and type II receptors are associated with this complex (14). We have recently identified the type I receptor and showed that, in vivo, it is required for import of type I as well as type II tRNAs (13).…”
Section: From the Genetic Engineering Laboratory Indian Institute Ofmentioning
confidence: 99%